Ellis family at daughter Faith's graduation, 1954 (Tufts Archival Research Center, 2005)
8 x 10 print, Ellis family at 1954 commencement left to right Sue, Dorie J31, Faith J54 and 'Fish' A29. Dorie played field hockey. Faith played basketball, field hockey, tennis and swimming.